Management Decisions in Crohn's Disease Are Changed by Knowledge of Proactive and Reactive Testing of Antitumor Necrosis Factor Drug Levels. Issue 3 (13th July 2021) - Wu, Yang; Wen, Amy; Selvanderan, Shane P; Xuan, Wei; Andrews, Jane M; Koo, Jenn H; Williams, Astrid-Jane; Ng, Watson; Connor, Susan
Abstract: Background: There is controversy about the proactive clinical application of therapeutic drug monitoring (TDM) of biologic drugs in Crohn's disease (CD). One way to practically assess this is to examine how TDM influences management decisions. We examined how knowledge of proactive and reactive antitumor necrosis factor (anti-TNF) drug levels changes management in a variety of clinical scenarios. Methods: In this retrospective cohort study, all adults with CD having trough level infliximab or adalimumab measurements at Liverpool Hospital between June 2013 and July 2016 were included. Demographics, indications for testing, anti-TNF drug levels, and treatment details were collected along with subsequent management decisions. The decision made by the treating clinician after receiving the drug level was compared to a consensus decision from a panel of 3 gastroenterologists based on the clinical, laboratory, imaging, and/or endoscopic results without the drug level. When these 2 decisions were discrepant, the anti-TNF drug level was deemed to have changed management. Results: One hundred and eighty-seven trough levels of infliximab or adalimumab from 108 patients were analyzed. Overall, assessment of anti-TNF levels affected management in 46.9% of the instances. Knowledge of the drug level was also more likely to result in management change when the test was performed for reactive TDM compared to proactive TDM (63% vs 36%, P = .001). Conclusions: The addition of TDM of anti-TNF agents to routine investigations alters management decisions in adult CD patients on anti-TNF therapy in both proactive and reactive settings. Lay Summary: A retrospective observational study that shows the addition of antitumor necrosis factor drug level to routine clinical parameters alters management decisions in adult Crohn's disease patients in both proactive and reactive settings.